Use of secondary dairy resources for the production of new products - Osmak, Anton; Bandura (Kuzmyk), Uliana (My University, 2024)
The analysis of literature shows that development of innovative whey technologies, and its complex use with food from animal and vegetable raw materials is a promising direction in the development of resource-saving food technologies.
Keywords: desserts; whey; сироватка молочна; кафедра технології молока і молочних продуктів